The aesthetics of reading and receiving in contemporary ceramics (Journal of the College of Basic Education, 2022)
This research is concerned with studying the aesthetics of reading and receiving in contemporary ceramics, and how the artist was able to convert them into means and tools that have an aesthetic and expressive value, and how he presented its surfaces, forms and display space. What are the aesthetics of reading and receiving in contemporary ceramics? The researcher determined the importance of research in the relationship between the aesthetics of reading and reception in the structure of ceramic work and the effectiveness of the impact and influence of that on the ceramic achievement, as well as revealing what is new in the world of ceramics from various ideas and methods. And the second chapter, which consisted of two sections as follows: In the first topic: reading and receiving in the concept. In the second topic: the aesthetics of reception in contemporary Iraqi ceramics. As for the third chapter, the researcher analyzed the works of some Iraqi potters according to the descriptive analytical method. As for the research community, the researcher reviewed what was available to him of the artworks that belong to the contemporary Iraqi ceramics. In the research community, the research community was identified with (75) images completed within the temporal limits of the research (2005-2019). And the research sample, the researcher chose the research sample, as the number of its models reached (3) in an intentional way. Then the research method, where the researcher followed the descriptive analytical method in analyzing the samples of the research sample. In the fourth chapter, he reached the results, including:The individuality of the work of the contemporary Iraqi potter is what makes it within the circle of modernity, who has taken his paths of experimentation with ceramic formations to reach a modernist feature that emphasizes the technical structural aspect.The artistic form of the contemporary ceramic piece contributes to a dialogue synthesis of the same form and the artist's style through the subject, the idea and the function.